Performance Models in Higher Education - Atkinson-Grosjean, Janet; Grosjean, Garnet (Education Policy Analysis Archives, 2000)
Higher education (HE) administrators worldwide are responding to performance-based state agendas for public institutions. Largely ideologically-driven, this international fixation on performance is also advanced by the operation of isomorphic forces within HE's institutional field. Despite broad agreements on the validity of performance goals, there is no "one best" model or predictable set of consequences. Context matters. Responses are conditioned by each nation's historical and cultural institutional legacy. To derive a generalized set of consequences, issues, and impacts, we used a comparative international format to examine the way performance models are applied in the United States, England, Australia, New Zealand, Sweden, and the Netherlands. Our theoretical framework draws on understandings of performance measures as normalizing instruments of governmentality in the "evaluative state," supplemented by field theory of organizations. Our conclusion supports Gerard Delanty's contention, that universities need to redefine accountability in a way that repositions them at the heart of their social and civic communities.